2017
DOI: 10.1021/acs.macromol.7b01428
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-Grafted Nanoparticle Membranes with Controllable Free Volume

Abstract: Polymer-based membranes play a key role in several industrially important gas separation technologies, e.g., removing CO 2 from natural gas, with enormous economic and environmental impact. Here, we develop a novel hybrid membrane construct comprised entirely of nanoparticles grafted with polymers. These membranes are shown to have broadly tunable separation performance through variations in graft density and chain length. Computer simulations show that the optimal NP packing forces the grafted polymer layer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
150
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(161 citation statements)
references
References 48 publications
11
150
0
Order By: Relevance
“…The immobilization of the AuNPs on the surface is supported by the fact that particle spacing is not affected (within experimental error) by subsequent thermal annealing (see Figure S6, Supporting Information). It has been reported that higher free volume can be achieved in PGNPs than in a melt of free polymer chains due to packing constraints . This indicates that simple geometric arguments that rely on constant density cannot be used to describe PGNP scaling.…”
Section: Resultsmentioning
confidence: 99%
“…The immobilization of the AuNPs on the surface is supported by the fact that particle spacing is not affected (within experimental error) by subsequent thermal annealing (see Figure S6, Supporting Information). It has been reported that higher free volume can be achieved in PGNPs than in a melt of free polymer chains due to packing constraints . This indicates that simple geometric arguments that rely on constant density cannot be used to describe PGNP scaling.…”
Section: Resultsmentioning
confidence: 99%
“…To illustrate the sasPDF method we have applied it to some representative nanoparticle assemblies from the literature (Nykypanchuk et al, 2008;Han et al, 2008;Bilchak et al, 2017). The first example is from DNA-templated gold nanoparticle superlattices, originally reported by Nykypanchuk et al (2008).…”
Section: Application To Representative Structuresmentioning
confidence: 99%
“…The molecular weight and density of the capping polymers can be varied and in the current sample were 0.47 chains nm À2 and 132 kDa, respectively. Studies had suggested that similar NPA samples exhibit no structural order, on the basis of an empirical metric using the height of the first peak in the measured SĂ°QÞ (Bilchak et al, 2017). Here we apply the sasPDF method to obtain a more complete understanding of the structure of this NPA.…”
Section: Tablementioning
confidence: 99%
“…Polymer-grafted solid or porous core particles are investigated with great interest for their use in adsorption [1], separation devices [2] and as components of hybrid membranes [3][4][5]. These hybrid particles can be packed into porous beds and they combine the intrinsic properties of the core particles and of the polymers grafted on them [6].…”
Section: Introductionmentioning
confidence: 99%